-32*4-2
=-32(4)-2
=4*-32-2
=4*+34
=4*34
=136.
Chat with our AI personalities
3 x 2 x 4 = 24 (3 x 2) x 4 = 6 x 4 = 24 3 x (2 x 4) = 3 x 8 = 24 2 x (3 x 4) = 2 x 12 = 24
2 x 2 x 2 x 2 x 3 x 3 2 x 2 x 2 x 2 x 9 2 x 2 x 3 x 3 x 4 2 x 2 x 36 2 x 4 x 18 2 x 2 x 2 x 3 x 6 2 x 2 x 4 x 9 2 x 8 x 9 2 x 2 x 3 x 12 4 x 4 x 9 4 x 6 x 6 3 x 3 x 16 3 x 4 x 12 2 x 6 x 12 3 x 3 x 4 x 4 2 x 3 x 24
3lnx - ln2=4 lnx^3 - ln2=4 ln(x^3/2)=4 (x^3)/2=e^4 x^3=2e^4 x=[2e^4]^(1/3)
Question: 2 x 3 x 4 Answer: It's easier to break this down into separate parts. First, multiply 2 x 3 = 6 Then multiply 6 (which is 2 x 3) x 4 = 24 Therefore, 2 x 3 x 4 = 24
x2 + x + 1 = 0 ∴ x2 + x + 1/4 = -3/4 ∴ (x + 1/2)2 = -3/4 ∴ x + 1/2 = ± √(-3/4) ∴ x = - 1/2 ± (i√3) / 2 ∴ x = (-1 ± i√3) / 2